Description of the methods for describing and assessing the appropriateness of antibiotic prescribing and adherence to published treatment guidelines in an academic medical clinic - Michael E Klepser; Ashley Altom; Colleen MacCallum; Eric Nordquist; Donald G Klepser (University of Minnesota Libraries Publishing, 2016)
Overuse and inappropriate use of antibiotics have been associated with increased rates of antimicrobial resistance and increased healthcare expenditures. Tracking inpatient antimicrobial use has helped quantify the value of stewardship programs aimed at improving the rational use of antibiotics among hospitalized patients. Unfortunately, similar methods for tracking and assessing antibiotic use in the outpatient setting have not been well described. We developed a novel method to capture trends and assess appropriateness of antibiotic usage. This strategy is based on identification of antimicrobial prescriptions in an electronic medical record system, linking prescribing to patient data, and capturing information regarding dosing and indications for use. Using information on dose, frequency, and duration of the antibiotic prescribed, a parameter to quantify antibiotic exposure (Prescribed Therapeutic Regimen, PTR) is calculated. This parameter is compared to a database of information on agents recommended in published guidelines (Recommended Therapeutic Regimen, RTR). By linking an ICD-9 code and the prescribed antibiotic we determine the appropriateness of the PTR by comparing it to the RTR for a given indication. Data are used to establish a baseline pattern of antibiotic use in the clinic to gauge the impact of future stewardship activities. Additionally, individual clinics and prescribers are given a snapshot of their antibiotic use compared to other clinics and prescribers. This is a novel means of describing antibiotic use in the outpatient setting that could serve as a standardized model for various adult and pediatric outpatient practices.   Type: Original Research